The Effect of Speed on Biomechanics of Walking and Running - Tsatalas Θεμιστοκλής; Tsaopoulos Δημήτριος; Sideris Βασίλης; Spyropoulos Γιάννης; Tsiokanos Αθανάσιος; Koutedakis Γιάννης; Giakas Γιάννης (Inquiries in Physical Education and Sport, 2016)
The purpose of this study was to review the existing literature regarding the effects of speed on walking and running biomechanics. The review was focused on spatiotemporal, kinematic, kinetic, and electromyographical data. Most of the examined parameters showed changes at different speeds. However, some specific parameters demonstrated changes reaching a plateau after a certain speed. The knowledge of biomechanics of human locomotion modes at different speeds could help sport scientists, medical doctors and physical therapists to implement more successful training regimens for athletes and enhances the quality of life of people with disabilities and musculoskeletal problems. Further research is needed to identify other factors and mechanisms that are responsible for the observed changes while walking and running at different speeds.